Investigation of multiple intelligence of primary school students - Lukman Nulhakim; Liska Berlian (Faculty of Mathematics and Natural Sciences, Universitas Negeri Yogyakarta, 2020)
The aim of this research is to investigate the ability of multiple intelligence (MI) of male and female students from primary school. The total sample was 71 students consisting of 35 experimental group students and 36 in the control group in a primary school in Cilegon City, 2016-2017 academic year. In this study, the experimental group consisted of male students using learning with the MI and the control group consisted of female students using learning with the MI approach. Analysis of data obtained from this study, using the Independent Sample t-test and Pearson Product Moment Correlation Coefficient. The findings of this study indicate that there is a statistically significant difference between the ability of MI in the experimental group and the control group, where the average score experimental group is higher. These results can be seen in the average score of MI ability in the experimental group is higher in visual-spatial, music, logical-mathematical, interpersonal and bodily-kinesthetic intelligence. The average score of MI ability in the control group is higher in verbal-linguistic, naturalistic, and intrapersonal. These concluded that the results of the Investigation of Multiple Intelligence (MI) of Primary School Students in the experimental group (male students) were better than the control group (female students).